The Climatic Quality Index Determination for Iraq Using Meteorological Stations Data - Jawad, Laith A. (Iraqi Journal of Science, 2022)
The drought is a globally phenomenon, its influence will convert large parts of Middle East and North Africa (MENA) region into hot dry deserts under the expectations of the climate change scenarios. Climate limitations, soil erosion affected by weather properties such as unequally and limited rainfall; temperature changing and wind, unsuitable irrigation techniques, excessive grazing, agricultural expansion against to the natural habitats, extensively clearance of natural vegetation, and soil salinity had all contributed to land degradation, reduced water supplies, and limited agricultural production in Iraq. It is estimated that nearly 54.3 % of Iraq’s area is threatened by desertification problems.In this research, for Iraq the Climatic Quality Index (CQI) has been utilized to state the arid and semi-arid lands area variation during the interval (1980-2012) using the meteorological data of eleven stations. The results shows that at the end of eighties decade the arid lands covered only 73% of Iraq’s area, and the arid lands covered 78% of Iraq’s area in the nineties decade, while in the first decade of the second millennium the arid lands rapidly increased to cover 88% of Iraq’s area. this search shows that the "Global Warming" was the reason beyond the temperature averages increments within last climate period which lead to arid regions rapidly extension in Iraq.